Program Magang Sebagai Upaya Peningkatan Soft Skill Mahasiswa Akuntansi Syariah Dalam Menghadapi Dunia Kerja - Laila Makhmudah; Saski Desi Astuti; Ilham Tegar Wahyu Nugroho; Siti Nurngaini (Pusmedia Group Indonesia, 2025)
This internship program aims to improve the soft skills of Sharia Accounting students in facing the world of work through practical experience at BMT ANDA Semarang. The internship activity is carried out for three months, including the stages of preparation, implementation, and reporting. During the internship, students are involved in various activities such as preparing Ramadan toolkits, packing parcels for employees and orphans, visiting the cash office, and archiving data. As a result, students not only gain technical skills such as administration and data analysis, but also develop soft skills such as accuracy, responsibility, and social concern. This program shows that internships are an effective method to prepare students to face the challenges of the world of work while strengthening sharia values in economic practices.